The new david espinoza ebook - Aceves, Fred (2020)
This story from the acclaimed author of The Closest I've Come unflinchingly examines steroid abuse and male body dysmorphia. Perfect for fans of Jason Reynolds and Matt de la Peña. David Espinoza is tired of being messed with. When a video of him getting knocked down by a bully's slap goes viral at the end of junior year, David vows to use the summer to bulk up— do what it takes to become a man—and wow everyone when school starts again the fall. Soon David is spending all his time and money at Iron Life, a nearby gym that's full of bodybuilders. Frustrated with his slow progress, his life eventually becomes all about his muscle gains. As it says on the Iron Life wall, What does not kill me makes me stronger. As David falls into the dark side of the bodybuilding world, pursuing his ideal body at all costs, he'll have to grapple with the fact that it could actually cost him everything. A Chicago Public Library Best Teen Fiction Selection A Banks Street Best Children's Book of the Year